EFEKTIVITAS PELAYANAN AKADEMIK MAHASISWA PADA MASA PANDEMI COVID-19 DI FISIP UIN AR-RANIRY BANDA ACEH - Saiful Akmal; Siti Nur Zalikha; Hani Emafita (Puslatbang KHAN, 2022)
In order to implement educational policies during the Covid-19 emergency period, the Minister of Education and Culture of the Republic of Indonesia released Circular Letter 4 of 2020 on March 24, 2020. Universitas Islam Negeri-Ar-Raniry Banda Aceh has also been affected by Covid-19, and they have decided that all academic activities and faculty services be completed online by all students. The purpose of this study is to evaluate the effectiveness of student academic services during Covid-19 and the factors that hinder and facilitate that effectiveness. In this study, we used a descriptive qualitative methodology with in-depth interviews conducted with the purposively selected informants. The findings demonstrated that, despite the availability of online resources, the effectiveness of student academic services during the Covid-19 pandemic was still insufficient. Goal attainment, integrity, and adaptation are three examples of service effectiveness metrics that have not been met. Despite this, service providers continue to work on enhancing their offerings, particularly in light of the Covid-19 outbreak.